Strategy as engagement: what organization strategy can learn from military strategy - Kornberger, M; Vaara, E (Elsevier, 2021)
Strategy process and practice research has illuminated the internal dynamics of strategy work – at the cost of backgrounding processes and practices that relate to engagement with external actors. In this conceptual paper, we argue for an extension of this body of work by shifting the locus of research from internal practices and processes towards externally oriented practices of engagement. We do so by critically building on the military strategy literature and develop the concept of strategy as engagement. This concept suggests understanding the role of strategy as bridge between policy and tactics; the importance of grand strategy as the making of policy; and the need to focus attention on tactics as distributed and collective action. The aim of the paper is to rejuvenate strategy process and practice research through 1) extending its repertoire to practices of engagement and 2) broadening its epistemic foundation through a critical reading of military strategy.